2019
DOI: 10.1039/c9sc03913a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning symmetry breaking charge separation in perylene bichromophores by conformational control

Abstract: Varying the structure of perylene-based dimers allows tuning the excited state from an excimer to a charge-separated state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 83 publications
(107 reference statements)
5
91
0
Order By: Relevance
“…Over the past few years, there has been a growing interest for symmetry-breaking (SB) charge transfer processes occurring in multichromophoric systems and multipolar conjugated dyes. [1] One of them, symmetry-breaking charge separation, occurs between two identical chromophores, [2][3][4][5][6][7][8][9][10][11][12][13] and offers interesting perspectives for applications in photovoltaics and artificial photosynthesis. [14,15] Here, electronic excitation can initially be entirely localised on one of the chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, there has been a growing interest for symmetry-breaking (SB) charge transfer processes occurring in multichromophoric systems and multipolar conjugated dyes. [1] One of them, symmetry-breaking charge separation, occurs between two identical chromophores, [2][3][4][5][6][7][8][9][10][11][12][13] and offers interesting perspectives for applications in photovoltaics and artificial photosynthesis. [14,15] Here, electronic excitation can initially be entirely localised on one of the chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…11 Macrocycles 1e and 1f used as reversible ratiometric luminescent switches and scaffolds to study targeted photophysical properties, respectively. 32,33 to ECD transitions cancelling each other. However, upon cation addition and binding, the overall number of conformations decreased and the novel conformationally-constrained geometries favored the inverted ECD signal(s) leading to the observed enhancement ( Fig.…”
Section: Effective Chiroptical Propertiesmentioning
confidence: 98%
“…It was demonstrated that the nature of the excited state varies greatly from an excimer to a symmetry-broken charge separated state depending on the conformational restrictions (cation binding) and the local environment. 33…”
Section: Luminescence Quenching Monitoringmentioning
confidence: 99%
“…The formation of excited charge transfer state depends on the mutual orientation and distance of the molecules. [35] For spatially separated excited charge transfer states, the oscillatory strength depends on certain degree of electronic wavefunction overlap. Besides, the intermolecular distance plays an important role, the degree of face-to face overlapping is also important for excitation of spatially separated charge transfer states.…”
Section: (D)mentioning
confidence: 99%